2018
DOI: 10.20965/jdr.2018.p0022
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Assessment of GPM Satellite Rainfall over Myanmar

Abstract: Intensive and long-term rainfall in Myanmar causes floods and landslides that affect thousands of people every year. However, the rainfall observation network is still limited in number and extent, so satellite rainfall products have been shown to supplement observations over the ungauged areas. One example is the estimates from Global Precipitation Measurement (GPM) called Integrated Multi-satellite Retrievals for GPM (IMERG), which has high spatial (0.1 × 0.1 degree) and temporal (30 min) resolution. This ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
3
1
0
Order By: Relevance
“…This was consistent with previous research in Bali showing a better correlation in the dry season in comparison to the rainy season [40]. Other observations in Myanmar [72] and Mekong River [74] also found similar results. Furthermore, the lowest correlation was shown in the DJF season (Figure 6a).…”
Section: Seasonal Assessmentsupporting
confidence: 93%
See 1 more Smart Citation
“…This was consistent with previous research in Bali showing a better correlation in the dry season in comparison to the rainy season [40]. Other observations in Myanmar [72] and Mekong River [74] also found similar results. Furthermore, the lowest correlation was shown in the DJF season (Figure 6a).…”
Section: Seasonal Assessmentsupporting
confidence: 93%
“…The same pattern was also found in the Maritime Continent region, such as in Singapore [25] and Malaysia [37] for IMERG-F. The patterns of overestimation of monthly rainfall were also found in areas near the Maritime Continent, such as in Myanmar [72] and Thailand [73]. However, in Malaysia the IMERG-E and IMERG-L data estimated lower rainfall than the rain gauges [37].…”
Section: Monthly Assessmentsupporting
confidence: 69%
“…The highest correlation was found in the JJA season (Figure 6c). This result is consistent with previous research in Bali, which found a better CC during the dry season compared to the rainy season, such as in Bali (Liu et al, 2020), East Asia (Lee et al, 2019), Myanmar (Mohsan et al, 2018), and the Mekong River (Wang et al, 2017). Meanwhile, a low CC was found during the DJF season (Figure 6a).…”
Section: Seasonal Assessmentssupporting
confidence: 92%
“…However, their accuracy diminished considerably when applied to decadal and daily values [10]. Various validation studies conducted in Southeast Asia have examined the compatibility between daily satellite products and rain gauge data [18,19]. These studies highlight the potential benefits of implementing bias correction techniques to enhance the quantitative alignment of rain rate values.…”
Section: Introductionmentioning
confidence: 99%